Bolstering the Biomedical Paradigm - Frank Thomas Houghton; Sharon B Houghton (Social Medicine Publication Group, 2014)
In this editorial, Drs. Frank Thomas Houghton and Sharon Houghton discuss JAMA's recent (2014) series on statistics and methods as evidence of an overemphasis on quantitative methodology in research and an ignoring of qualitative methods.